2018
DOI: 10.3892/ol.2018.8081
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor microRNA‑136‑5p regulates the cellular function of renal cell carcinoma

Abstract: Abstract. MicroRNAs (miRs) are involved in diverse physiological and developmental processes at the post-transcriptional level in cells. Previous studies have demonstrated that miR-136-5p is involved in certain types of cancer. However, the function of miR-136-5p in renal cell carcinoma (RCC) remains to be fully elucidated. In present study, miR-136-5p expression levels were determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and MTT assays, CCK-8 assays, Transwell assays, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(37 reference statements)
1
22
0
Order By: Relevance
“…Taheriazam et al (33) demonstrated that miRNA-130b expression was increased in OS tissues, whereas, the level of miRNA-218 expression was downregulated; these miRNAs may serve as potential biomarkers in the early detection of OS. In this study, it was indicated that the expression of miR-136 was downregulated in the patients with OS, which is consistent with the results in previous studies (34,35). For instance, miR-136 was downregulated and acted as a tumor suppressor in colon cancer (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taheriazam et al (33) demonstrated that miRNA-130b expression was increased in OS tissues, whereas, the level of miRNA-218 expression was downregulated; these miRNAs may serve as potential biomarkers in the early detection of OS. In this study, it was indicated that the expression of miR-136 was downregulated in the patients with OS, which is consistent with the results in previous studies (34,35). For instance, miR-136 was downregulated and acted as a tumor suppressor in colon cancer (34).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, miR-136 was downregulated and acted as a tumor suppressor in colon cancer (34). In renal cell carcinoma, miR-136 was reported to be downregulated and associated with renal cell carcinoma cellular functions (35). To improve the understanding of the role of miR-136 in OS, its expression patterns and association with the clinicopathological features of the patients with OS were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-136-5p was reported to serve as a tumor-suppressive miRNA in renal cell carcinoma and has the potential to be used as biomarker for early detection and prognosis prediction. 16 In addition, miR-136-5p was found decreased expression in lung squamous cell cancer and it may interact with UGT1A7 and ADH7 to regulate cellular metabolism processes. 17 We validated the direct connection of FOXP4-AS1 and miR-136-5p using luciferase activity reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of this micro-RNA is inversely correlated with the stage/grade and the metastatic potential of tumors and mammary cell lines. Hsa-miR-136-5p is also described for its tumor suppressor role in the context of prostate cancer, renal carcinomas, pulmonary adenocarcinomas or osteosarcomas [91][92][93][94][95].…”
Section: Post-transcriptional Regulation Of the Expression Of Erα36 Bmentioning
confidence: 99%